Whistleblowing sebagai Strategi Peningkatan Tata Kelola Perusahaan - Puspa Setia Arum Sari (Politeknik Ganesha Medan, 2023)
Efforts to implement good corporate governance are often hindered by various types of cases such as acts of fraud, causing large losses and disrupting corporate governance. Prevention of fraud cases is very important to prevent this impact. This research focuses on the description of the literature about the importance of implementing whistleblowing in improving corporate governance, especially preventing fraud in a company. This research is a type of qualitative research using the library research method with the content analysis approach. The results of the study describe that the use of whistleblowing in several private and public companies proves the important role of whistleblowing in achieving effective corporate governance. Whistleblowing actions taken not only resulted in the dismissal of parties proven to be involved in fraudulent transactions, but also contributed significantly to the emergence of whistleblowing as an effective corporate governance mechanism. The implications of this research can be used as new insights on the use of whistleblowing for corporate governance that is able to minimize fraud in the future